Phylogenetic relationships of the genus Lachenalia with other related liliaceous taxa - Spies, Paula (University of the Free State, 2015)
Lachenalia is a small bulbous geophyte of the family Hyacinthaceae, endemic to South Africa and first described in 1787 by Jacquin. There is a large degree of variation in the genus and some species overlap morphologically with other genera such as Polyxena and Massonia , and it is very difficult to delimit the species. There are currently approximately 120 species described, but new species are frequently described. Several authors attempted to subdivide the genus (Baker, 1897; Crosby, 1986; Duncan, 1988 & 2002). Lachenalia has a tremendous cultivation potential, and 25 new cultivars have been introduced since 1966. A cytogenetic, as well as a molecular study, was conducted to try and solve problems with the classification in the genus, and to provide answers to the breeders regarding infertility problems between interspecific crosses. The chromosome numbers of a few species were determined by examining meiotic and mitotic chromosomes in order to guide the breeders in their hybridisation studies. The numbers obtained during this study were combined with results of previously studies to try and determine the original basic chromosome number(s) in the genus. Several basic chromosome numbers have been reported in the genus, i.e. x = 5/10, 7, 8, 9, 11 and 13. The majority species have a basic chromosome number of x = 7, followed by x = 8 and then x = 11. Polyploidy is common, occurring in 40% of the species in the genus. The number x = 7 has mainly diploids, 28.6% tetraploids and a few hexa - and octaploids and, therefore, represents a young mature polyploid complex. The numbers x = 8 and x = 11 both forms young polyploid complexes. According to this information, it can be concluded that x = 7 were the original basic number, from which x = 8 and x = 11 evolved. The hypothesis on the evolution of the chromosome numbers were tested by sequencing the trnL-F region of the chloroplast genome. This region was also sequenced to try and provide answers for the taxonomists on the difficult task of classifying and delimiting the genus. The phylogenetic position of the genus in relation to other liliaceous plants also needed to be determined. The basic chromosome numbers were superimposed on the cladogram, and a definite correlation between chromosome numbers and monophyletic groups were obtained. Several monophyletic clades formed, dividing the cladogram into four distictive groups: the “L. juncifolia”, “Lachenalia 1”, “Lachenalia 2” and “L. zebrina” groups, and several subgroups. The position of these groups and subgroups confirms the hypothesis that x = 8 evolved from x = 7. It also indicated that several hybrids prevail within the genus, explaining the delimitation problems and the variation in basic chromosome numbers. The genus Polyxena are included within the Lachanalia clade, indicating that this genus should either be included in the genus, or Lachenalia should be split into several genera. Polyxena could also have introduced new chromosome numbers and variation in the genus by hybridisation. The cladogram confirms that Polyxena is the closest relative of Lachenalia , followed by Massonia and Whiteheadia . This study indicated that the cytogenetic and molecular data support one another. The trnL-F region is useful to study phylogenetic relationships on genus or higher taxonomic levels, but the addition of other genes will probably provide more answers for the classification and evolution of the genus.

Lachenalia is ‘n klein bolplant van die familie Hyacinthaceae. Dit is endemies tot Suid -Afrika en is reeds in 1787 deur Jacquin beskryf. Die genus bevat geweldig baie variasie en oorvleuel morfologies met die genera Polyxena en Massonia . Spesie-afbakening in die groep is baie moeilik. Tans is ongeveer 120 spesies beskryf en nuwe spesies word dikwels beskryf. Verskeie outeurs het gepoog om die genus te onderverdeel (Baker, 1897; Crosby, 1986; Duncan, 1988 & 2002). Lachenalia het ‘n uitstekende kultiveringspotensiaal en 25 nuwe kultivars is reeds sedert 1966 vrygestel. ‘n Gekombineerde sitogenetiese en molekulêre studie is onderneem om die klassifikasieprobleme van die genus te probeer oplos. ‘n Verdere doel van die studie was om te probeer om die onvrugbaarheidsprobleme by basters tussen verskillende spesies te begin aanspreek vir die telers. Chromosoomgetalle van ‘n paar spesies is bepa al deur mitotiese en/of meiotiese studies om sodoende telers te help met moontlike kruisings beplanning. Die chromosoomgetalle waargeneem tydens hierdie studie is saam met die beskryfde getalle in die literatuur gevoeg in ‘n poging om die oorspronklike bas iese chromosoomgetal van die genus te probeer bepaal. Verskeie basiese chromosoomgetalle is reeds vir die genus gerapporteer, nl. x = 5/10, 7, 8, 9, 11 en 13. Die meeste spesies het ‘n basiese getal van x = 7, gevolg deur x = 8 en x = 11. Poliploïdie is ‘n algemen verskynsel onder 40% van die spesies in die genus. Spesies met ‘n basiese getal van sewe is meestal diploïed met 28.6% tetraploïedes en ‘n paar heksa- en oktaploïedes. Hierdie spesies verteenwoordig dus ‘n jong volwasse poliploïede kompleks. Spesies met basiese getalle van 8 en 11 verteenwoordig altwee jong poliploïede komplekse. Hierdie data suggereer dat x = 7 die oorspronklike basiese getal verteenwoordig, waaruit x = 8 en x = 11 ontwikkel het. Hierdie hipotese oor die basiese chromosoomgetal is getoets deur dit te vergelyk met die filogenie verkry uit die nukleotiedvolgordes vanaf die trnL-F streek van die chloroplaste genoom. Hierdie streek se volgordes is ook bepaal om die taksonomiese probleme in die genus te probeer oplos. Die filogenetiese posisie van Lachenalia in die lelieagtiges is ook bepaal. Die basiese chromosoomgetalle is met die kladogramme gekombineer. Die kombinasie toon duidelik dat die basiese chromosoomgetalle met die verskillende monofeletiese takke van die boom ooreenstem. Die monofeletiese takke wat gevind is kan in vier duidelike groepe onderverdeel word, nl. die “L. juncifolia”, “Lachenalia 1”, “Lachenalia 2” en “L. zebrina” groepe. Verskeie subgroepe kan onderskei word. Die posisie van die groepe en subgroepe steun die hipotese dat x = 8 uit x = 7 ontwikkel het. Dit dui ook op die moontlikheid dat verskeie basters in die genus bestaan, derhalwe die probleme met spesie-afbakening en die verskillende basiese chromosoomgetalle. Die genus Polyxena is ingesluit in die Lachanalia tak. Dit dui daarop dat Polyxena in Lachenalia ingesluit moet word of dat laasgenoemde in verskeie genera onderverdeel moet word. Polyxena kon nuwe chromosoomgetalle tot Lachenalia gevoeg het deur verbastering. Die bome bevestig dat Polyxena die naaste ve rwant is aan Lachenalia, met Massonia en Whiteheadia as ander verwantes. Die sitogenetiese en molekulêre data ondersteun mekaar. Die trnL-F streek is bruikbaar vir filogenetiese studies op genusvlak of hoër, maar meer gene moet bestudeer word om die klassifikasie en evolusie van die genus uit te klaar.
Dissertation (M.Sc.Agric. (Plant Sciences: Genetics))--University of the Free State, 2004
Keywords: Chromosome numbers; DNA sequencing; Evolution; Hyacinthaceae; Lachenalia; Phylogenetic relationships; Polyploidy; Aneuploidy; Lachenalia -- Phylogeny; Liliaceae -- Phylogeny